Polymicrobial bacterial or fungal infections: incidence, spectrum of infection, risk factors, and clinical outcomes from a large hematopoietic stem cell transplant center. Issue 2 (April 2015) - Trifilio, S.; Zhou, Z.; Fong, J.L.; Zomas, A.; Liu, D.; Zhao, C.; Zhang, J.; Mehta, J.
Abstract: Background: Infections cause significant morbidity and mortality for patients who undergo hematopoietic stem cell transplantation (HSCT). Cancer patients who develop polymicrobial infection (PI) are at increased risk for poor clinical outcomes, yet very limited data have been published within the HSCT setting. Methods: An observational study of 901 stem cell transplant recipients was conducted at Northwestern Memorial Hospital to identify the incidence, risk factors and outcomes for HSCT recipients who develop infection(s) with multiple bacterial or fungal organisms. Results: Among 901 HSCT recipients reviewed (675 autografts and 226 allografts), 237 patients (27%) had microbiologically documented microorganisms isolated, including 179 patients (76%) with monomicrobial infection and 59 patients (24%) with multiple microorganisms, of which 34 (14%) were classified as PI, and 25 (10%) as multiple distinct episodes of infection. Conclusion: The results show co‐infection with multiple organisms during HSCT is relatively rare; however, these patients are at an increased risk for the development of acute graft‐versus‐host disease, delayed engraftment, and overall mortality.